2022
DOI: 10.1002/cphc.202200010
|View full text |Cite
|
Sign up to set email alerts
|

Substituent Effects in π‐Hole Regium Bonding Interactions Between Au(p‐X‐Py)2Complexes and Lewis Bases: Anab initioStudy

Abstract: Long range substituent effects in regium bonding interactions involving Au(I) linear complexes are investigated for the first time. The Au(I) atom is coordinated to two para-substituted pyridine ligands. The interaction energy (RI-MP2/def2-TZVP level of theory) of the π-hole regium bonding assemblies is affected by the pyridine substitution. The Hammett's plot representations for several sets of Lewis bases have been carried out and, in all cases, good regression plots have been obtained (interaction energies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…In this way, MESP is able to account for various types of substituent effects, including the classical inductive and resonant effects [28–30] . Likewise, MESP has been used with excellent results to account for long range substituent effects in π‐hole regium bonding interactions [33] …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, MESP is able to account for various types of substituent effects, including the classical inductive and resonant effects [28–30] . Likewise, MESP has been used with excellent results to account for long range substituent effects in π‐hole regium bonding interactions [33] …”
Section: Methodsmentioning
confidence: 99%
“…[27] The molecular electrostatic potential (MESP) has been shown to be a suitable theoretical tool for studying the effects of chemical substituents in π-conjugated molecular systems. [28][29][30][31][32][33] This is because the substituents affect the electron density to some extent and this is noticeably reflected in the MESP. MESP is particularly affected in atomic centers where some kind of chemical activation or deactivation is expected under the presence of a chemical substituent group attached to another atom located in some strategic position of the molecule.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that M 2 –benzene complex (M = Cu, Ag, or Au) undergoes Rg−π interactions whereas MCl–benzene complexes (M = Cu, Ag, or Au) tend to shift toward cation−π interactions . The initial survey of protein data bank (PDB) and Cambridge structural database (CSD) has revealed that Rg−π bonds are present in Au­(I)–protein complexes and dicoordinated linear Au­(I) complexes . A secondary survey of PDB and CSD has discovered that Rg−π bonds of Cu and Ag are also present in biological as well as supramolecular structures, where noble metals (Cu and Ag) act as the Rg−π donor and various aromatic moieties such as pyridine, cyanobenzene, etc., act as the Rg−π acceptor.…”
Section: Introductionmentioning
confidence: 99%
“…While numerous model studies have been performed on the nature and energetics of the Rg−π bond of Au, , Rg−π bonds of Cu and Ag are still a gray area. Here, we report a detailed computational study to investigate the nature and energetics of Rg−π bonds using the RgL–X model system, where Rg = Cu and Ag; L = CN, NO 2 , OH; and X = π-conjugated system (benzene, cyanobenzene, benzoic acid, pyridine, 2-methoxy aniline, 1,4-dimethoxy benzene, and cyclophane) (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, quantitative relationships have been derived in certain classes of systems and usefully applied where the binding energy can be simply related to one or more indicators derived from these methods. For example, it is common in the literature to consider the bond critical point density as a measure of bond strength [23][24][25][26][27] and possibly even with spectroscopic perturbations. 28 In an alternate scheme, the energies of some of these bonds are sometimes assessed via a simple relationship with the potential energy density 24,[29][30][31] or other quantities extracted from AIM analysis.…”
Section: Introductionmentioning
confidence: 99%